Insight into bubble nucleation at high-pressure drop rate. (September 2017) - Tammaro, Daniele; Iannace, Salvatore; Di Maio, Ernesto
This paper presents insight in bubble nucleation in polymer foaming with physical blowing agent using a batch foaming technique. In our experiments the bubble nucleation is triggered by a sudden pressure drop that causes the supersaturation in the polymer gas solution. In fact, the pressure drop rate is an important process variable since it plays a role in both bubble nucleation and growth. Herein, we investigated very high pressure drop rates, and confirmed the great importance of the pressure drop rate as foaming process variable. The results show that the number of nucleated bubbles increases of one order of magnitude and the foam density is reduced if the pressure drop rate is increased from 50 to 500 MPa/s. Interestingly, the number of nucleated bubble increases linearly in a bi-logarithmic scale as function of pressure drop rate at all the investigated temperatures. Moreover, in the current paper, it is discussed how talc used as nucleating agent plays a role in cooperation with pressure drop rate on bubble nucleation at different foaming temperatures.